Persepsi Kegunaan, Persepsi Kemudahan Penggunaan, serta Faktor Keamanan dan Kerahasiaan pada Minat Penggunaan E-Filling - Suryani, Made Dwi Ananda; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2022)
The renewal effort carried out by the DJP is through modernization to increase tax revenue, namely through E-Filling. E-Filling is issued by the DJP to facilitate the work of taxpayers in submitting Annual Tax Returns online and real time. The purpose of this study is to obtain real and empirical evidence regarding the interest in using E-Filling which is influenced by perceived usefulness, perceived ease of use, and security and confidentiality factors. The location of this research was taken at KPP Pratama Gianyar. The research sample was 100 effective and registered WPOPs using E-Filling taken using the Slovin with the accidental sampling, whose data were collected using a questionnaire. The analysis technique uses multiple linear regression analysis with the help of SPSS 23. The results of the study explain where the influence of perceived usefulness, perceived ease of use, as well as security and confidentiality factors indicate a positive and significant direction on interest in usingE-Filling as a tax reporting system. Keywords: Perception of Usefulness; Perceived Ease of Use; Security and Confidentiality Factors; E-Filling